Agricultural Development: The Role Of Government in Agricultural Development (Article Review) - M. Eka Wijaya; Fuji Kacaya Mita; Evo Afrianto; Asminar Asminar (Fakultas Pertanian Universitas Muara Bungo, 2022)
Agricultural development is a process aimed at continuously increasing agricultural production in order to increase agricultural production for each consumer, which at the same time increases the income and business productivity of each farmer by increasing capital and skills to increase human involvement in the development of crops. plants and animals. Agricultural development is an integral part of economic development and society in general. Broadly speaking, agricultural development is not just a process or activity to increase agricultural production but is a process that produces social changes in values, norms, behavior, institutions, social and so on in order to achieve economic growth and improve the welfare of farmers and society. Agriculture is the main sector producing food ingredients and industrial materials that can be processed into clothing, food, and board materials that can be consumed or traded, therefore agricultural development is part of economic development.